2011
DOI: 10.1016/j.bcp.2011.07.093
|View full text |Cite
|
Sign up to set email alerts
|

Green tea catechin, epigallocatechin-3-gallate (EGCG): Mechanisms, perspectives and clinical applications

Abstract: An expanding body of preclinical evidence suggests EGCG, the major catechin found in green tea (Camellia sinensis), has the potential to impact a variety of human diseases. Apparently, EGCG functions as a powerful antioxidant, preventing oxidative damage in healthy cells, but also as an antiangiogenic and antitumor agent and as a modulator of tumor cell response to chemotherapy. Much of the cancer chemopreventive properties of green tea are mediated by EGCG that induces apoptosis and promotes cell growth arres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
906
2
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,293 publications
(941 citation statements)
references
References 92 publications
23
906
2
10
Order By: Relevance
“…Such inhibitors have attracted attention for the development of new drugs against amyloidoses 2,3 . A promising anti-amyloidogenic compound is the antioxidant molecule epigallocatechin-3-gallate (EGCG), the major green tea polyphenol which displays neuroprotective and anticancerogenic effects in cellular and animal models 4,5 . EGCG redirects AS aggregation into offpathway, non-toxic, SDS-resistant, spherical and nanostructured oligomers of ~20-nm diameter 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Such inhibitors have attracted attention for the development of new drugs against amyloidoses 2,3 . A promising anti-amyloidogenic compound is the antioxidant molecule epigallocatechin-3-gallate (EGCG), the major green tea polyphenol which displays neuroprotective and anticancerogenic effects in cellular and animal models 4,5 . EGCG redirects AS aggregation into offpathway, non-toxic, SDS-resistant, spherical and nanostructured oligomers of ~20-nm diameter 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Along with enzymatic activities, different endogenous compounds like glutathione, plasma protein thiols and iron-binding proteins are needed to maintain the oxidative balance. Dietary components, like vitamins and polyphenols, also contribute in maintaining intracellular redox homeostasis [26,27]. An increasing numbers of studies have demonstrated that GTPs are strong antioxidant compounds [21,28], nonetheless GTPs are also able to exert pro-oxidant effects.…”
Section: Effects Of Gtcs On Cellular Redox Homeostasis and Antioxidanmentioning
confidence: 99%
“…The antioxidant properties of the GTCs are due to the presence of both the phenolic groups and the galloyl moiety, that allow electron delocalization, and free radical quenching ability. Accordingly to their structural features, EGCG and ECG are, among the four most abundant GTCs, the strongest antioxidants [27,32]. However, GTCs may undergo auto-oxidation reactions, leading to the formation of catechin dimers and free radicals that may be responsible of the pro-oxidant action observed in vitro after polyphenols administration.…”
Section: Effects Of Gtcs On Intracellular Ros Productionmentioning
confidence: 99%
“…However, a widely recognized problem in the therapeutic application of EGCG is the large variability in the bioavailability of orally administered EGCG (reviewed in [108] and [112]). This is owing to its high sensitivity to oxidation, the tendency to conjugate to proteins in the digestive tract (e.g., casein), and rapid metabolism in the body.…”
Section: Perspectives For Prevention and Therapymentioning
confidence: 99%